2016
DOI: 10.1108/ijhcqa-07-2015-0083
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Lean bundles on hospital performance: does size matter?

Abstract: Structured Abstract: Purpose: The purpose of this research is to study the effect of the implementation of lean bundles on hospital performance in private hospitals in Jordan and evaluate how much the size of organization can affect the relationship between lean bundles implementation and hospital performance. Design/Methodology/Approach: The research is considered as quantitative method (descriptive and hypothesis testing). Three statistical techniques were adopted to analyse the data. Structural Equation Mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
41
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 56 publications
(119 reference statements)
3
41
1
1
Order By: Relevance
“…performance of hospital departments and target realized work program by Bakar et al (2009), Bhat et al (2016), Al-Hyari et al (2016), Warburton et al (2004); and…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…performance of hospital departments and target realized work program by Bakar et al (2009), Bhat et al (2016), Al-Hyari et al (2016), Warburton et al (2004); and…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have found partial relationship between variables such as: service performance and financial performance by Duncan and Elliott (2004), Camarero (2007), Liang et al (2009), Keisidou et al (2013); customer performance and financial performance by Chotekorakul and Nelson (2013), Eklof et al (2017), Moon and Choi (2014); growth and learning performance and internal business process performance by Lee et al (2011), Kotey and Anderson (2006), Bititci et al (2011), Liu and Tsai (2007), Jusoh et al (2008), Tung et al (2011); growth and learning performance and performance of hospital departments by Potter et al (1994), Chen et al (2006), Halkjær and Lueg (2017), Capkun et al (2012); performance of hospital departments and target realized work program by Bakar et al (2009), Bhat et al (2016), Al-Hyari et al (2016), Warburton et al (2004); and performance of hospital departments and performance appraisal of hospital departments by Coates (1996), Wilson and Western (2000), Pantouvakis and Mpogiatzidis (2013). …”
Section: Introductionmentioning
confidence: 99%
“…A crescente utilização e adaptação do Lean no setor da saúde, especialmente no ambiente hospitalar, tem gerado o que é conhecido como Lean Healthcare. As intervenções Lean no setor da saúde visam melhorar a qualidade da saúde, reduzindo assim o desperdício e facilitando o fluxo nos processos de trabalho (Shazali et al, 2013;Andersen et al, 2014;Al-Hyari et al, 2016).…”
Section: Introductionunclassified
“…CI has been widely used by both the manufacturing and service sectors to achieve the abovementioned and to gain a competitive advantage by implementing programs that minimize product cost, reduce waste in both human effort and inventory, create faster delivery time and become highly responsive to the demand of customers while producing superior quality products, thus significantly impacting competitiveness and organizational performance (Singh and Singh, 2018; Jasiulewicz-Kaczmarek and Saniuk, 2017; Arya and Jain, 2014; Al-Hyari et al , 2016).…”
Section: Introductionmentioning
confidence: 99%